Measuring Income Inequality and Implications for Economic Transmission Channels - Blotevogel, Robert (IMF Working Papers; Working Paper, 2020)
We study the channels that theoretically transmit the effects of inequality to economic growth, unlike much of the existing literature that focuses on the direct linkage. The role of inequality in these transmission channels is difficult to pin down and varies with the particular inequality indicator chosen. We run our analyses with six methodologically distinct inequality measures (Gini coefficients and Top10 income shares). Methodological differences within the set of Gini coefficients and the Top10 income shares exert a first-order impact on the estimated relationships, which is generally larger than the effect of switching between Gini and Top10 income shares. For a given inequality indicator, we find that the transmission channels can react in opposite directions, with the net effect on growth difficult to determine. Finally, we emphasize two additional but so far underappreciated empirical complications: (i) estimated relationships change over time; and (ii) fragile countries create significant but counterintuitive empirical associations that may obscure structural relationships.